Effectiveness Of Pt Good Doctor Technology Indonesia's Partnership Strategy And Communication Pattern With Partner Companies - Arif Wihananto; Akrom Arroisi; Silmi Kafa Hanifa Azzahra (International Journal Labs, 2024)
This research discusses how the strategy and pattern of partnership communication carried out by PT Good Doctor Technology Indonesia with various forms of companies in order to provide telemedicine health services to all Indonesian people. With this research, it also has a goal to know and understand how the strategy and communication pattern are implemented, in order to worship the vision of PT Good Doctor Technology Indonesia, namely